Prove: A & B => C => [A => [B => C]] Suppose... 1 A & B => C Premise Prove: A => [B => C] Suppose... 2 A Premise We have two cases to consider: 3 B | ~B Or Not Case 1 ------ Prove: B => [B => C] Suppose... 4 B Premise Prove: B => C Suppose... 5 B Premise 6 A & B Join, 2, 4 7 C Detach, 1, 6 As Required: 8 B => C Conclusion, 5 Case 1 ------ As Required: 9 B => [B => C] Conclusion, 4 Case 2 ------ Prove: ~B => [B => C] Suppose... 10 ~B Premise 11 ~B | C Arb Or, 10 12 ~~B => C Imply-Or, 11 13 B => C Rem DNeg, 12 Case 2 ------ As Required: 14 ~B => [B => C] Conclusion, 10 Joining results for Cases rule... 15 [B => [B => C]] & [~B => [B => C]] Join, 9, 14 In both cases... 16 B => C Cases, 3, 15 As Required: 17 A => [B => C] Conclusion, 2 As Required: 18 A & B => C => [A => [B => C]] Conclusion, 1